Phosphorylated pullulan promotes calcification during bone regeneration in the bone defects of rat tibiae - Morimoto, Yasuhito; Hasegawa, Tomoka; Hongo, Hiromi; Yamamoto, Tomomaya; Maruoka, Haruhi; Haraguchi-Kitakamae, Mai; Nakanishi, Ko; Yamamoto, Tsuneyuki; Ishizu, Hotaka; Shimizu, Tomohiro; Yoshihara, Kumiko; Yoshida, Yasuhiro; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
The current study aimed to evaluate bone tissue regeneration using a combination of -triphosphate calcium (TCP) and phosphorylated pullulan (PPL, a phosphate-rich polysaccharide polymer consisting of maltotriose units). Round defects of 2 mm diameter were created in the arterial center of rat tibiae, which were further treated with vehicle (control group), TCP (TCP group), or TCP+PPL (TCP+PPL group) grafts. The control specimens without bone grafts exhibited rapid bone formation after one week; however, the regenerated bone was not resorbed until four weeks. In contrast, TCPgrafted specimens exhibited fewer but thicker trabeculae, whereas the TCP+PPL group displayed 2 This is a provisional file, not the final typeset article many fine trabeculae at four weeks. In the TCP+PPL group, new bone was associated with the βTCP granules and PPL. Similarly, PHOSPHO1-positive osteoblasts were localized on the TCP granules as well as the PPL. On the other hand, TRAP-reactive osteoclasts predominantly localized on newlyformed bone and TCP granules rather than on the PPL. No significant differences were observed in the expression of Alp, Integrin v, Osteopontin, Osteocalcin, and Dmp-1 in PPL-treated MC3T3-E1 osteoblastic cells, suggesting that PPL did not facilitate osteoblastic differentiation. However, von Kossa staining identified abundant needle-like calcified structures extending inside the PPL. Furthermore, transmission electron microscopy (TEM) revealed many globular structures identical to calcified nodules. In addition, calcified collagen fibrils were observed in the superficial layer of the PPL. Thus, PPL may serve as a scaffold for osteoblastic bone formation and promotes calcification on its surface. In conclusion, we speculated that TCP and PPL might promote bone regeneration and could be integrated into promising osteoconductive materials.